1997
DOI: 10.1007/s004310050752
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in mothers with pregestational diabetes: a population-based study in North Rhine (Germany) from 1988 to 1993

Abstract: The prevalence of births from mothers with pregestational diabetes and their pregnancy outcomes were similar to those in other Western countries. The standard for non-diabetic mothers has not been reached yet. Further improvements may be achieved if all diabetic women are convinced to use the standard prenatal care facilities throughout pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 16 publications
(17 reference statements)
3
24
1
2
Order By: Relevance
“…These results differ from the results of studies in the United Kingdom and Poland: congenital malformations in infants whose mothers had pre-existing diabetes were found in 9.4 and 11.2%, respectively [7,9]. On the other hand, a study from Germany showed congenital malformations in 2.1% of such infants [2]. A large prospective study done in 1990 has shown that infants of insulin-dependent mothers are 8 times more likely to have a major malformation [13].…”
contrasting
confidence: 62%
“…These results differ from the results of studies in the United Kingdom and Poland: congenital malformations in infants whose mothers had pre-existing diabetes were found in 9.4 and 11.2%, respectively [7,9]. On the other hand, a study from Germany showed congenital malformations in 2.1% of such infants [2]. A large prospective study done in 1990 has shown that infants of insulin-dependent mothers are 8 times more likely to have a major malformation [13].…”
contrasting
confidence: 62%
“…Type I diabetes mellitus (DM) affects approximately 0.2% to 0.4% of all pregnancies [68,69]. Diabetic pregnancy is a high-risk obstetric situation [70,71]; 30% of diabetic women with no observable DR, and 70% with background diabetic retinopathy (BDR) at the inception of pregnancy develop obstetric complications [72].…”
Section: Epidemiologymentioning
confidence: 99%
“…Most of the research on pregestational diabetes and pregnancy outcomes has focused on type 1 diabetes (3,4). However, in many regions of the world, the number of pregnancies in women with type 2 diabetes is exceeding that of type 1 diabetes (5,6).…”
mentioning
confidence: 99%